COVID-19 pandemic response behaviors: a Singapore experience of the "circuit breaker". Issue 3 (8th March 2021) - Chew, Han Shi Jocelyn; Chng, Samuel
Abstract: Preventive health behaviors such as hand hygiene are crucial amidst pandemics like COVID-19 but reports on nonadherence persist. This could be due to the lack of Consideration of Future Consequences (CFC), a cognitive-motivational construct known to improve health-related behaviors. Therefore, we examined the relationship between CFC and five behaviors—mask-wearing, social distancing, hand hygiene, excessive necessities buying, and COVID-19 information searching using an internet-based Singapore-wide survey conducted from April 20 to May 4, 2020. Behavioral differences 2 weeks before and after the state-wide confinement were examined using paired t-tests. Relationships between CFC and COVID-19 behaviors were examined using regression analyses adjusted for depression and anxiety. Participants were regrouped into three categories—increased behavior performance, maintained high performance, and maintained low performance where mean differences were analysed using MANOVA. Three hundred and thirty-six participants completed the survey (mean age, SD = 32.9 years [ SD = 12.6]; 38.7% males). CFCfuture predicted mask wearing ( B = 0.16; p < .05), social distancing ( B = 0.0.19; p < .01), hand hygiene ( B = 0.17; p < .01), and information searching ( B = 0.21; p < .001). CFCimmediate predicted hand hygiene ( B = 0.09; p < .05), excessive necessities buying ( B = 0.07; p < .05) and information searching ( B = 0.08; p < .05). Anxiety predicted excessive buying ( B = 0.08; p < .05) and hand hygiene ( B = 0.13; p < .01). Post-hoc test showed significantly higher CFCfuture ( p < .01) in participants who increased and maintained high behavioral performance.